Sharpening species boundaries in the Micarea prasina group, with a new circumscription of the type species M. prasina. (4th July 2019) - Launis, Annina; Malíček, Jiří; Svensson, Måns; Tsurykau, Andrei; Sérusiaux, Emmanuël; Myllys, Leena
ABSTRACT: Micarea is a lichenized genus in the family Pilocarpaceae (Ascomycota). We studied the phylogeny and reassessed the current taxonomy of the M. prasina group. We focused especially on the taxonomic questions concerning the type species M. prasina and, furthermore, challenges concerning type specimens that are too old for successful DNA barcoding and molecular studies. The phylogeny was reconstructed using nuc rDNA internal transcribed spacer region (ITS1-5.8S-ITS2 = ITS), mitochrondrial rDNA small subunit (mtSSU), and replication licensing factor MCM 7 gene from 31 species. Fifty-six new sequences were generated. The data were analyzed using maximum parsimony and maximum likelihood methods. The results revealed four undescribed, well-supported lineages. Three lineages represent new species described here as M. fallax, M. flavoleprosa, and M. pusilla . In addition, our results support the recognition of M. melanobola as a distinct species. Micarea fallax is characterized by a vivid to olive green thallus composed of aggregated granules and whitish or brownish apothecia sometimes with grayish tinge (Sedifolia-gray pigment). Micarea flavoleprosa has a thick, wide-spreading yellowish green, whitish green to olive green sorediate thallus and lacks the Sedifolia-gray pigmentation. The species is mostly anamorphic, developing apothecia rarely. Micarea melanobola is characterized by a pale to dark vivid green granular thallus and darkly pigmented apothecia (Sedifolia-gray). Micarea pusilla is characterized by a whitish green to olive green thinly granular or membranous thallus, numerous and very small whitish apothecia lacking the Sedifolia-gray pigment, and by the production of methoxymicareic acid. Micarea fallax, M. flavoleprosa, and M. melanobola produce micareic acid. The reliability of crystalline granules as a character for species delimitation was investigated and was highly informative for linking the old type specimen of M. prasina to fresh material.